Scale-up strategies in stirred and aerated bioreactor - Zainal Alam, Muhd. Nazrul Hisham (2005)
The scale-up studies based on the constant oxygen transfer coefficient (kLa) from 16 liter to 150 liter of aerated and agitated bioreactor were performed. The studies included the investigation on the significance of hydrodynamic difference between Rushton and marine impeller on the kLa at 16 liter scale. By employing both static and dynamic gassing out techniques, the kLa values were calculated at different sets of impeller speeds and air flow rates performed in various viscosities and temperatures in the 16 liter and 150 liter BioengineeringTM stirred bioreactor. Empirical correlation was employed to correlate and investigate the dependence of kLa on specific power input and superficial air velocity. Our experimental results discovered that the Rushton turbine was more effective in gas distribution and provide a greater oxygen transfer rate than the marine impeller. In maintaining a constant kLa upon scale-up from 16 to 150 liter, the specific power input and the superficial air velocity cannot be maintained, adjustment has to be done. Specific power input from 0.0001 to 4.2 kW/m3 and superficial air velocity within the range of 9 x 10-4 to 7 x 10-3 m/s was tested to maintain a constant value of kLa upon scaleup in distilled water and CMC solution model. The operating variables employed at 150 liter scale successfully gave a comparable kLa values as in 16 liter scale. Hence, the calculated scaling-up factor for impeller speed and air flow rate were 0.28 and 3.1, respectively. In order to investigate the potential of employing scaling-up protocol developed in this work, the kinetic profiles of E.coli batch fermentation at 16 and 150 liter were compared. By employing the scaling-up factors, the proposed scale-up protocol managed to provide the similar trend of cell growth, glucose consumption and oxygen uptake rate upon scale-up based on the constant kLa. It may be concluded that the similar kLa for both scales was successfully achieved by employing the proposed scale-up protocol.